Preparation And Characterization Of Kenaf Filled Natural Rubber Latex Foam - Karim, Ahmad Fikri Abdul (2019)
Kenaf fiber have attracted great interest as filler material in polymer matrix composites (PMC) due to its low cost, and the ability to enhance properties such as tensile strength and modulus, chemical resistance and thermal stability of PMC. However, poor dispersion and incompatibility of kenaf in NRLF still remain as challenging issue for their practical application in various environment. In this research kenaf filled NRLF composite containing 0 to 7 part per hundred rubbers (phr) of kenaf loading was prepared through a well-known Dunlop processing method. Kenaf filled NRLF shows reduction of tensile properties, swelling resistance and thermal stability properties of kenaf filled NRLF composites as compared to the unfilled NRLF. The less physical interaction via penetration and/or interlocking of NRLF chains at kenaf surface contributed to weak interfacial adhesion between kenaf and NRLF which leads to the decreased in properties of kenaf filled NRLF composites. However, with some modification to the kenaf and NRLF, the properties of kenaf filled NRLF were improved. Studies on the partial replacement of kenaf by starch were carried out to determine the potential of starch as replacement for kenaf in NRLF composites. Series of five composites of kenaf/starch filled NRLF composites with different kenaf/starch fraction loading (i.e. 7/0, 5/2, 3.5/3.5, 2/5 and 0/7 phr) were prepared. Partial replacement of kenaf by starch produced hybrid filler composites showed great potential as co-filler with kenaf NRLF composites, at which the tensile properties, swelling resistance, compression and hardness was improved with increased in starch fraction. The thermal stability was higher at 3.5/3.5 kenaf/starch fraction. Based on this series of studies, the corn starch was then used as a co-filler in the formulation of kenaf filled NRLF with fix amount of starch (3 phr). The results show that the tensile strength, elongation at break, swelling resistance, hardness, thermal stability and density were higher compared with samples without corn starch. The morphological study by SEM shows that samples with co-filler have smaller pores size and better distribution. The effect of treated kenaf by alkaline treatment on the properties of kenaf filled NRLF composites were then studied separately. The dispersion of kenaf in NRLF and interfacial adhesion between kenaf and NRLF was further enhanced with the addition of treated kenaf, which enhanced tensile properties, hardness, compression, thermal stability and swelling resistance of the kenaf filled NRLF composites. The used of prevulcanized NRL shows the improvement of several properties of kenaf filled NRLF. The results show that 24 hours was the optimum time for prevulcanization of NRL. By comparing with samples without prevulcanized, samples with prevulcanized NRLF shows higher tensile properties, swelling resistance, density, hardness and thermal stability due to the crosslink density effects. Morphological study by using SEM shows the good interfacial adhesion and uniform pores size of kenaf filled prevulcanized NRLF.